2022
DOI: 10.1177/21514593211070688
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Analysis for Fat Infiltration in the Lumbar Paraspinal Muscles in Patients With Lumbar Degenerative Diseases

Abstract: Introduction This study aimed to investigate factors related to fat infiltration in patients with lumbar degenerative diseases (lumbar disc herniation and/or spinal stenosis), examining a wide range of potential risk variables. Materials and methods We studied consecutive adult patients who underwent posterior lumbar spinal surgery for degenerative diseases at our hospital between July 2013 and June 2017. Preoperative magnetic resonance imaging was used to evaluate the presence or absence of fat infiltration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The results presented by Gruber et al ( 25 ) showed that with increasing age, the healing process of the outer plate after surgery was not be enough to effectively reconstruct the outer ring, and the lower back muscles were atrophied in older patients than in younger patients and the muscle group's support for the lumbar spine was weakened, which was more likely to cause postoperative recurrence of intervertebral disc herniation. In addition, the study by Suzuki et al ( 26 ) found that the elderly were also more prone to lumbar muscle strain and paraspinal muscle fat infiltration. All these factors are related to long-term chronic low back pain, and postoperative recurrence and low back pain will cause postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented by Gruber et al ( 25 ) showed that with increasing age, the healing process of the outer plate after surgery was not be enough to effectively reconstruct the outer ring, and the lower back muscles were atrophied in older patients than in younger patients and the muscle group's support for the lumbar spine was weakened, which was more likely to cause postoperative recurrence of intervertebral disc herniation. In addition, the study by Suzuki et al ( 26 ) found that the elderly were also more prone to lumbar muscle strain and paraspinal muscle fat infiltration. All these factors are related to long-term chronic low back pain, and postoperative recurrence and low back pain will cause postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus on the L4/5 level was based on reports suggesting a higher susceptibility to fat infiltration in the lower lumbar vertebrae than in the upper lumbar vertebrae. 19 ) This method, which has been validated by several previous studies, 20 , 21 , 22 , 23 , 24 ) categorizes fat infiltration in the paraspinal muscles into three grades based on the amount of fat within the paraspinal muscles: grade 0, 0%–10%; grade 1, 10%–50%; and grade 2, >50%. This assessment was conducted visually using MRI ( Fig.…”
Section: Methodsmentioning
confidence: 99%